Propuesta de un sistema de registro a distancia de la frecuencia cardiorrespiratoria en aves - Leybón Ibarra., J.; Contreras Hernández., E.; Arch Tirado., E.; Alfaro Rodríguez., A. (Revista Mexicana de Ingenieria Biomedica, 2008)
Avians manipulation for cardio-respiratory rhythm recording is complicated because of the stress induced since the animal is captured until it is immobilized to attach the measurement instruments to him, and this process could be finalized in death. The development of instruments to register remote physiology signals is important for animal care and research applications. It is described the development and application of a pulse oximetry based electronic system to record the cardio-respiratory rhythm in small avians by using transcutaneous infrared light sensor taking advantage of the animal behavior and the cage arrangement to make the avian stand over the sensor spontaneously avoiding the behave and conduct disturb for added stimulus. A light and noise isolated area was designated to improve the pulse oximetry technical disadvantages and to diminish avian disturbing, getting quality records according to the daylight routine activity while the avian placement varies if the feet or stomach are next to or over the photoelectric devices. Results according to the avian placement respective to the photoelectric devices show three different signal patterns: heart rate, respiratory rhythm and the heart rate modulated by the respiratory rhythm. It is important to take into account as is considered in electroencephalographic tests the constant vigilance during the recording to set tags for the movement artifacts like smarten up and during the birdsong.